A lack of authentic school improvement plan development: Evidence of principal satisficing behavior. Issue 3 (13th May 2019) - Meyers, Coby Vincent; VanGronigen, Bryan Alexander
Abstract : Purpose: School improvement planning, especially for low-performing schools, can be conceptualized as a planning process to strategically improve organizational processes, operations and outcomes. However, bureaucratic procedures and related inflexibilities sometimes results in inauthentic plan development. The purpose of this paper is to analyze the extent and ways in which principals engage in satisficing behavior – or being in the realm of "good enough" – when developing school improvement plans (SIPs). Design/methodology/approach: The authors qualitatively analyzed 364 short-cycle SIPs submitted by principals of 134 low-performing schools participating across three cohorts of a university-based systems leadership program focused on change leadership and school turnaround. Findings: Eight satisficing behaviors in the SIPs were identified. The five most prominent satisficing behaviors follow: plan content is consistent across schools within a district; a plan or plan features are resubmitted; plan priorities focus solely on test scores; plan timeline is insufficiently considered; and the directly responsible individual (DRI) (to complete tasks) is insufficiently considered. Overall, 80 percent of SIPs contained two to four satisficing behaviors, and fewer than ten SIPs were free of such behaviors or, in the authors' estimation, completely authentic. Originality/value: The development of SIPs is mandated for the nation's lowest-performing schools, but little analysis of such plans has been conducted over the last 20 years. Moreover, although the notion that principals engage in satisficing behavior has been raised previously, to the authors' knowledge, this is the first study to systematically identify ways in which principals satisfice.